Descriptive Memoir of Planning Commission. (1st April 1954) Government of India - Planning Commission (Planning Commission, 1954)
The Planning Commission was established by a Resolution of the Government of India dated March 15th, 1950. It commenced work on March 28th, 1950 functions. The terms of reference of the Commission are: — to make an assessment of the material, capital and human resources of the country, including technical personnel and to investigate the possibilities of augmenting such of these resources as are found to be deficient in relation to the nation’s requirement; to formulate a Plan for the most effective and balanced utilisation of the country’s resources.
Government of India, Cabinet Secretariat (O. and M. Division)